The legacy of architect Leonid Chernyshev after a century - Merkulova, Maria; Slabukha, Alexander; Uspenskaya, Olga; Yamaletdinov, Sergey; Medievsky, Vladimir (project baikal, 2025)
The purpose of this article is to draw the attention of contemporaries to the architectural attractiveness of the city of Krasnoyarsk, which was formed by L. A. Chernyshev and other architects at the turn of the 19th and 20th centuries, and which allows Krasnoyarsk to be perceived as a provincial city with all its attributes. The article examines the views on the creative legacy of the outstanding Siberian architect Leonid Alexandrovich Chernyshev, his place and role in the modern environment of the city and professional interference to the works of Krasnoyarsk architects, researchers of Chernyshev’s work. The article is being published on the eve of the 150th anniversary of the architect. It was decided that the year 2025 in Krasnoyarsk will be dedicated to architect L. A. Chernyshev.
Keywords: architecture of Krasnoyarsk; Siberian architect; the works of architect L. A. Chernyshev; Yeniseisk provincial engineer and architect